Contrasting responses of vascular plants and bryophytes to present and past connectivity in unmanaged grasslands - Järvenpää Suvi; Kytöviita Minna-Maarit; Pitkämäki Tinja; Lampinen Jussi (Springer, 2022)
The area of semi-natural grasslands has decreased dramatically causing many grassland specialist species to persist in small habitat fragments. Furthermore, ecological communities once shaped by disturbances related to traditional agriculture now face the impacts of modern agriculture and urbanization. Many of the species have become endangered due to the combined effects of habitat destruction and degradation. We studied the responses of vascular plants and bryophytes to present and past connectivity in semi-natural grasslands, while accounting for the effects of local environmental conditions. We conducted vegetation surveys in 33 fragmented, unmanaged dry grasslands in Southwest Finland. A total of 191 vascular plant species and 60 bryophyte species were recorded. Higher vascular plant diversity was associated with higher historical connectivity, whereas bryophyte diversity declined with increasing current connectivity. Edaphic conditions, microclimate and disturbances were found to structure both vascular plant and bryophyte communities, but the responses to individual environmental variables were very different. The contrasting responses could be explained by the differences between the typical life-history strategies in vascular plants and bryophytes as well as resource competition between the two groups. These results highlight the need to consider different species groups when planning conservation measures. Vascular plant richness may best be conserved in connected grasslands whereas bryophyte richness in isolated ones. The results also indicated that trampling by humans could result in positive disturbance and to some extent help maintain richness of grassland specialist species.